2011
DOI: 10.1073/pnas.1103125108
|View full text |Cite
|
Sign up to set email alerts
|

Molecular serum portraits in patients with primary breast cancer predict the development of distant metastases

Abstract: The risk of distant recurrence in breast cancer patients is difficult to assess with current clinical and histopathological parameters, and no validated serum biomarkers currently exist. Using a recently developed recombinant antibody microarray platform containing 135 antibodies against 65 mainly immunoregulatory proteins, we screened 240 sera from 64 patients with primary breast cancer. This unique longitudinal sample material was collected from each patient between 0 and 36 mo after the primary operation. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
65
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 72 publications
(70 citation statements)
references
References 40 publications
2
65
0
1
Order By: Relevance
“…Investigators found an increase in serum levels of IL-9 over time in patients that later developed metastatic lesions, suggesting a relationship between IL-9 and tumor progression, or tumor load (23). …”
Section: Introductionmentioning
confidence: 99%
“…Investigators found an increase in serum levels of IL-9 over time in patients that later developed metastatic lesions, suggesting a relationship between IL-9 and tumor progression, or tumor load (23). …”
Section: Introductionmentioning
confidence: 99%
“…To this end, we have designed and applied a recombinant antibody microarray targeting mainly immunoregulatory analytes [23, 24]. Previously we have demonstrated the potential of our array design for cancer diagnosis [27], evidence-based therapy selection [28], as well as predicting the risk for breast cancer recurrence [30]. In this discovery study, we have extended the range of applications, and indicated its potential use for risk group stratification in PC, clearly differentiating the two lowest versus the highest risk groups.…”
Section: Discussionmentioning
confidence: 99%
“…We have demonstrated that the platform could be used to identify candidate biomarker signatures for e.g. diagnosis, prognosis, classification, and for evidence-based therapy selection [2730]. …”
Section: Introductionmentioning
confidence: 99%
“…We concur with Chechlinska’s argument that most cancer prognostic biomarker studies using modern technologies are methodologically flawed as they compare samples from cancer patients with those of healthy, inflammation-free people [20] or at best with those of patients with already metastasised tumours. In validation studies, it is important to determine whether the patient has dormant disease, and what type of mechanism is active, together with his or her systemic inflammatory response [21]. …”
Section: Discussionmentioning
confidence: 99%